Synthesis and biological evaluation of the [d-MeAla11]-epimer of coibamide A. Issue 2 (15th January 2015) - Nabika, Ryota; Suyama, Takashi L.; Hau, Andrew M.; Misu, Ryosuke; Ohno, Hiroaki; Ishmael, Jane E.; McPhail, Kerry L.; Oishi, Shinya; Fujii, Nobutaka
Graphical abstract: Abstract: Coibamide A is a highly potent antiproliferative cyclic depsipeptide, which was originally isolated from a Panamanian marine cyanobacterium. In this study, the synthesis of coibamide A has been investigated using Fmoc-based solid-phase peptide synthesis followed by the cleavage of the resulting linear peptide from the resin and its subsequent macrolactonization. The peptide sequence of the linear coibamide A precursor was constructed on a solid-support following the optimization of the coupling conditions, where numerous coupling agents were evaluated. The macrocyclization of the resulting linear peptide provided the [d -MeAla 11 ]-epimer of coibamide A, which exhibited nanomolar cytotoxic activity towards a number of human cancer cell lines.